Análise de Compostos Fenólicos e Potencialantioxidante de Amostras Comerciais de Sucos de Uva e Produtos Derivados de Uvas Venícolas - Silva, Anna Débora Ferreira da (2010)
Phenolic compounds are widely found in the plant kingdom. Among the fruits considered as functional foods, grapes and their derivatives are always in a position of prominence, especially after the association of regular consumption of wine to a healthy life. This work was carried out in order to know the antioxidant properties and resveratrol concentration of grape juices and also of grape pomace samples, a byproduct of winemaking. The skins of wine grapes Vale São Francisco (varieties Syrah and Cabernet Sauvignon), the Syrah grape pomace and commercially available grape juices were studied for their profile of polyphenolic compounds and antioxidant activity. Samples were taken from sun-exposed grape Syrah, coded as sol and grape shade by the foliage canopy, coded as sombra ." The juice samples were composed 11integrals juices,8 reprocessed grape juice and 11 nectars. An extract of grape and pomace was prepared from 0,5mg of sample (dry weight) with 3 ml of a solution of ethanol / water (80/20 v / v). The concentration of the cis and trans-isomers of resveratrol were determined by using a chromatographic method (HPLC-UV/DAD with C8 chromatography column) and spectrophotometric methods were determined phenolic monomeric anthocyanins and DPPH radical scavenging activity (expressed as EC50 μg / mL ). The trans isomer of resveratrol was determined in samples of Syrah sombra , Cabernet Sauvignon, Syrah pomace and on 60% of the juices analyzed. The isomer cis of resveratrol was determined only on the samples Syrah grape sol and this isomer was not found in the nectar juice samples. The total phenolic for grapes ranged between 3,7 and 17,59 ± 0.05 ± 0,61 mg / mL for wine grapes and from 451,7 ± 4,68 and 1935,0 ± 15,06 g / mL for grape juices. Grape pomace was determined in 3268,0 ± 360.7 mg / mL (n = 3). Monomeric anthocyanins for grapes ranged from 1,47 ± 0,08 and 10,0 ± 0,56 mg / mL for wine grapes and between 6,88 ± 0,63 and 292,4 ± 27,7 mg/L the grape juices. In the pomace was determined 0,75 ± 0,07 mg/mL (n = 3). The Syrah grape pomace showed high antioxidant activity (EC50 1,09 μg/mL) compared to ascorbic acid (EC50 2,12 ± 0,0009 μg/mL) The Syrah grape sol and sombra showed significant differences regarding their ability to scavenge the DPPH radical. The results obtained allow us to conclude that the not only the polyphenolic content, but also their profile, influenced the antioxidant activity of the sample. The Syrah grape pomace had a very high content of total phenolics and radical-scavenging activity, and is thus a potential source of these substances that deserve to be used.